Designing an Online Train Ticket Booking Website Using the Design Thinking Method - Cania, Dea; Triandi, Budi (Jurnal ICT : Information and Communication Technologies, 2025)
The increasing demand for train services in Indonesia has highlighted significant challenges in conventional ticket reservation systems, including long queues, limited customer time, scheduling errors, and rapid ticket depletion during peak periods. This study aims to develop and evaluate a digital train ticket reservation application designed to streamline booking processes, improve user experience, and provide real-time access to ticket availability, pricing, and schedules. The research employs a user-centered Design Thinking approach to guide the development of key functional modules, including login, train and route management, schedule creation, order processing, and user profile management. Results demonstrate that the application successfully integrates these functionalities into a unified platform, reducing operational inefficiencies, minimizing user errors, and enabling users to book tickets conveniently from multiple devices. The system enhances administrative oversight through centralized order reporting and data management, while improving overall service reliability and user satisfaction. These findings imply that human-centered digital platforms can transform traditional public transportation services by increasing operational efficiency, scalability, and customer convenience. Furthermore, the study identifies areas for future improvement, such as incorporating predictive analytics for demand forecasting, dynamic seat allocation, and extended accessibility features to accommodate diverse user needs. The results provide practical insights for railway operators seeking to implement adaptive, reliable, and user-friendly ticket reservation systems, underscoring the value of integrating technology, usability, and real-time information in public transport services.